Answer:
The dog weighs 16 pounds, while the cat weighs 8 pounds
Step-by-step explanation:
Let's call the weight of the dog d, and the weight of the cat c.
d+c=24
d=2c
Substitute the second equation into the first:
(2c)+c=24
3c=24
c=8
d=24-8=16
Hope this helps!
Answer:
A) 4
Step-by-step explanation:
There are a couple of ways to get this but this is how I did it:
1. Multiply the second equation by 1/4 to get the same fraction for y as the one in the first equation
1/4 x + 1/8 y = 2
1/4 (1/3 x + 1/2 y = 4)
1/12 x + 1/8 y = 1
2. Subtract the first equation from the new equation
1/12 x + 1/8 y = 1
<u> - 1/4 x - 1/8 y = -2</u>
-1/6 x= -1
3. Divide both sides by -1/6
<u>-1/6</u> x= <u>-1</u>
-1/6 -1/6
x = 6
4. Substitute 4 in for x in the original equation:
1/4 (6) + 1/8y = 2
6/4 + 1/8y = 2
1/8y = 1/2
y = 4
Answer:
Graph is below
Step-by-step explanation:
I graphed the point on the graph below.
Yeah I’m just like Albert